dynamic and cultural meanings of Tudmoei Kaebon Ceremonyin Khao Panom District, Krabi and Thungyai District, Nakonsritammarat - ณ ศรีสุข ศิรินภา; ตุลารักษ อุมารินทร์ (Journal for Developing the Social and Community, 2016)
This research study aimed to investigate dynamics and cultural meaning communication of Tudmoei Kaebon Ceremony in KhaoPanom District, Krabi and Thungyai District, Nakonsritammarat. The finding reveal that this ceremony was regarded as the important and sacred event for southern people. Participants of the ceremony will be offered sacrificial offerings (spirit) from KrueMor or KrueMor Ta-Yai (their ancestor) to treat mental and physical illnesses. At the stage of the ceremony, it has the dynamics and cultural meaning communication which is underlying in oblation. In addition, the ceremony reflects the southern’ customs and beliefs seen as the tool to console people’ feeling from threatening things as well as bring a sense of harmony within the communities. Most importantly, Tudmoei Kaebon ceremony will be promoted and inherited from generation to generation.